2016
DOI: 10.1007/s12020-016-1104-5
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin levels measured at the time of remnant ablation to predict response to treatment in differentiated thyroid cancer after thyroid hormone withdrawal or recombinant human TSH

Abstract: The objective of our study was to evaluate the prognostic value of stimulated thyroglobulin levels at the moment of remnant ablation for predicting an initial excellent or a structural incomplete response to treatment according to the risk of recurrence in patients with differentiated thyroid cancer. Patients were divided into two groups according to the preparation mode for remnant ablation (thyroid hormone withdrawal or recombinant human TSH). We included 219 patients followed-up for at least for 24 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
11
1
1
Order By: Relevance
“…Therefore, it is possible to identify a subset of thyroid cancer with poor uptake from the first radioiodine treatment by combining high A-hTg levels with absent or reduced uptake at WBS postradioiodine treatment. We did not find any significant difference regarding the performance of AUC cut-off of stimulated A-hTg ablation prepared by THW or Thyrogen in comparison with the work of Pitoia et al [19] and Ciappuccini et al [18]. In addition, the modality of preparation for radioiodine treatment (THW vs. Thyrogen) was not significant in the Cox regression analysis with respect to persistent disease.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Therefore, it is possible to identify a subset of thyroid cancer with poor uptake from the first radioiodine treatment by combining high A-hTg levels with absent or reduced uptake at WBS postradioiodine treatment. We did not find any significant difference regarding the performance of AUC cut-off of stimulated A-hTg ablation prepared by THW or Thyrogen in comparison with the work of Pitoia et al [19] and Ciappuccini et al [18]. In addition, the modality of preparation for radioiodine treatment (THW vs. Thyrogen) was not significant in the Cox regression analysis with respect to persistent disease.…”
Section: Discussioncontrasting
confidence: 75%
“…Recently, some authors have proposed a value of ablation hTg (A-hTg) lower than 10 ng/ml as a favourable factor on the subsequent disease-free status [16]. Additionally, different retrospective studies have confirmed this predictive prognostic value [1719].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the main factors affecting the thyroglobulin level include the amount of residual thyroid tissue or cancer lesion, TSH level, the time after the operation, and the thyroid hormone withdrawal time (39). These affecting factors can be closely related to each other.…”
Section: Discussionmentioning
confidence: 99%
“…At follow-up, there was no significant difference in treatment response whether under rhTSH-aided or THW-aided. In recent study by Pitoia et al [20] , 62.7% of patients under rhTSH-aided RA showed no evidence of disease and 15.7% of patients showed SIR. Although the characteristics of study population was different and the number of high-risk patients was relatively smaller in our study, it is likely that prophylactic CND yields better response profiles, probably at the cost of increased incidence of complications like hypoparathyroidism in our study.…”
Section: Discussionmentioning
confidence: 99%